Eliminating Blindness in Sri Lanka: Challenges and Options - Dissanayake, M.M. (Faculty of Medicine, University of Colombo, 2020)
Globally 2.2 billion people have vision impairment. Majority of the blind live in the developing world. In Sri Lanka...
Keywords: Blindness; Sri Lanka